2017
DOI: 10.1053/j.gastro.2016.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Hippo Signaling in the Liver Regulates Organ Size, Cell Fate, and Carcinogenesis

Abstract: The Hippo signaling pathway, also known as the Salvador–Warts–Hippo pathway, is a regulator of organ size. The pathway takes its name from the Drosophila protein kinase, Hippo (STK4/MST1 and STK3/MST2 in mammals), which, when inactivated, leads to considerable tissue overgrowth. In mammals, MST1 and MST2 negatively regulate the transcriptional co-activators yes-associated protein 1 (YAP) and WW domain containing transcription regulator 1 (WWTR1/TAZ), which together regulate the expression of genes that control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
228
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(237 citation statements)
references
References 127 publications
(172 reference statements)
7
228
1
1
Order By: Relevance
“…When the hepatocyte‐specific gene expressions in HepG2 were determined by RT‐PCR analysis, the highly mobile SPE‐PRX surfaces have higher gene expression levels than the less mobile SPE‐PRX surfaces. It has been reported that the cytoplasmic YAP localization contributed to the proliferation, survival and maintenance of hepatic functions, which is consistent with our results. Furthermore, the albumin secretions from cells were remarkably promoted by highly mobile SPE‐PRX surfaces with immobilized HB‐EGF.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…When the hepatocyte‐specific gene expressions in HepG2 were determined by RT‐PCR analysis, the highly mobile SPE‐PRX surfaces have higher gene expression levels than the less mobile SPE‐PRX surfaces. It has been reported that the cytoplasmic YAP localization contributed to the proliferation, survival and maintenance of hepatic functions, which is consistent with our results. Furthermore, the albumin secretions from cells were remarkably promoted by highly mobile SPE‐PRX surfaces with immobilized HB‐EGF.…”
Section: Discussionsupporting
confidence: 94%
“…For instance, rigid materials induce nuclear translocation of yes‐associated proteins (YAPs) in hepatocytes to activate Hippo‐signaling pathways, although soft materials inhibit this translocation. Nuclear localization of YAPs induces the dedifferentiation, fibrosis, and apoptosis of hepatocytes, whereas cytoplasmic localization of YAPs affects the maintenance or modulation of proliferation, survival, and other functions . Accordingly, it is imagined that in vitro hepatic functions are improved by not only adding growth factors but also modulating the surface properties of substrates.…”
Section: Introductionmentioning
confidence: 99%
“…However, the highest relative expression of WWC1 and WWC2 was detected in periportal hepatocytes and small hepatic cells surrounding the portal vein (http://onlinelibrary.wiley.com/doi/10.1002/hep.29647/suppinfo). Interestingly, this expression pattern is very similar to the spatial gradient of YAP cotranscriptional activity seen within the hepatic lobule, in which the highest YAP activity is found close to portal triads . Furthermore, our in situ hybridization results are consistent with earlier proteomic data for mouse liver, which indicated that WWC1 and WWC2 proteins are found in hepatocytes, Kupffer cells, liver sinusoidal endothelial cells, hepatic stellate cells, and cholangiocytes (http://onlinelibrary.wiley.com/doi/10.1002/hep.29647/suppinfo).…”
Section: Resultssupporting
confidence: 88%
“…C) analyses of liver sections from dKO mice confirmed an increase of cells with nuclear YAP compared with control sections in which YAP displayed a mainly cytoplasmic localization in hepatic cells. As mentioned earlier, the cotranscriptional activity of YAP in the liver is known to be highest in periportal hepatocytes and biliary cells and lowest in the area close to the central vein . Accordingly, nuclear YAP localization in the dKO livers was found only in periportal cells (Fig.…”
Section: Resultssupporting
confidence: 60%
“…Upon triggers such as the loss of cell‐cell contact, disturbed cell polarity, or mechanical stress, MST1/2‐LATS1/2 activities decline, and so does proteasomal degradation of YAP1. Accumulating YAP1 then can translocate to the nucleus where it acts—in concert with TAZ—as a transcriptional coactivator to promote the expression of its target genes such as Birc5 or Ctgf . The release of YAP1 activity usually is associated with cell cycle entry and apoptotic suppression resulting in an enlarged organ …”
Section: Introductionmentioning
confidence: 99%